Factors associated with caesarean section at Bukavu Provincial Hospital in Democratic Republic of Congo - Philémon, Mulongo Mbarambara; Julie, Mwamini Chumbika; Ntakwinja, Mukanire; Célestin, Kyambikwa Bisangamo; Théodore, Mvula Mwantito (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Caesarean section is the most common major surgery performed on women Worldwide. Even if caesarean can be useful for mother and foetus, it can provoke some medical and social complications like infection, expensive cost and maternal death. This study aimed at determining the factors associated with caesarean section in Bukavu, at the Provincial Hospital. Methods: Data were collected retrospectively by exploring the files of childbirth established systematically for each pregnant woman. 466 files were exploited including 233 caesarean s (case) and 233 vaginal delivery (control). The normal childbirth which followed a caesarean was served as control. This study was a case-control. Logistic regression was used to model factor associated with caesarean section. Results: During the study period, there were 2170 deliveries in which 491 of them by caesarean section (22.6%). The factors associated with the caesarean section at the Provincial Hospital in Bukavu town were foetal distress, bleeding in the third trimester of the pregnancy, previous caesarean section, referral status and the moment of delivery (day shift). Conclusion: This study recommends an adequate monitoring of the pregnancy and training of professionals in best practices; implementation and technical audit of caesarean with feedback can significantly reduce the rate of Caesarean section in this hospital. Also, allocation in equipment suitable for the treatment of pregnant women is necessary.